Pengaruh Akreditasi Untuk Meningkatkan Mutu Pelayanan dan Keselamatan Pasien di Rumah Sakit (Studi Sistematik Review) - Raysella Khaulla Miandi; Yuly Peristiowati (Akademi Perekam dan Informasi Kesehatan Imelda, 2022)
Hospital accreditation is a government recognition of hospitals that have met the standards that have been set to get an idea of the extent of meeting hospital standards in Indonesia, so that the quality of service can be accounted for. The purpose of review research is systematic to find out the influence of accreditation in improving the quality of service and patient safety in hospitals. The research design used in this study is Systematic Review. The purpose of this method is to help researchers better understand the background of the research that is the subject of the topic sought and understand why and how the results of the study so that it can be a reference for new research. Independent variables are accreditation and variable dependents, namely the quality of hospital services and the safety of hospital patients. Researchers conducted a search for data through the websites of accessible journal portals such as PubMed, Elsevier, Springer, and Google Schoolar. The results showed after the collection of journals using accredited journal sites such as PubMed, Elsevier, Springer, and Google Schoolar. 496 journals were identified and eligibility criteria were carried out. Then after it was filtered obtained 23 journals, then excluded studies were obtained 3 journals met the exclusion criteria, after that based on inclusion criteria so that the total number of articles eligible for review was 20 articles. Quality improvement in all fields, especially in the field of health, one of which is through Hospital Accreditation towards the quality of International services. In the accreditation system that refers to the Standards of the Joint Commission International (JCI) obtained the most relevant standards related to the quality of hospital services International Patient Safety Goals (international targets of patient safety) which includes six hospital patient safety goals.